2016
DOI: 10.1007/s10792-016-0356-7
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of higher-order aberrations and anterior segment tomography in patients with pathologic myopia

Abstract: Highly myopic eyes had higher-order aberrations than emmetropic eyes because of the increasing internal aberrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…Some other studies were only concerned with the evaluation of myopia-related HOAs. Kasahara et al [33] estimated HOAs in patients with pathological myopia and found that highly myopic eyes had more HOAs than emmetropic eyes because of the increased internal aberrations. Karimian et al [34] also concluded that primary horizontal trefoil, spherical aberrations, and primary vertical coma were the predominant HOAs in eyes with myopic astigmatism.…”
Section: Discussionmentioning
confidence: 99%
“…Some other studies were only concerned with the evaluation of myopia-related HOAs. Kasahara et al [33] estimated HOAs in patients with pathological myopia and found that highly myopic eyes had more HOAs than emmetropic eyes because of the increased internal aberrations. Karimian et al [34] also concluded that primary horizontal trefoil, spherical aberrations, and primary vertical coma were the predominant HOAs in eyes with myopic astigmatism.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of HOAs can cause significant night vision problems including glare, haze, and halos. HOAs are related to the scotopic pupil size [20], the treatment optic zone [21], and the preoperative refraction [22]. Spherical aberration is usually accepted as a single aberration that is most closely affected by the degree of myopic correction performed.…”
Section: Discussionmentioning
confidence: 99%
“…However, many of these reported associations have been inconsistent, as they have been confounded by varying patient selection, variability in definitions of myopia and the use of different imaging techniques 59. Although most of the refractive error associated with myopia comes from the axial length, it is increasingly recognised that changes of the anterior segment in high myopia lead to significant optical and higher order aberrations 60. A potentially interesting aspect is the study of biomechanical changes associated with corneal thickness in high myopia, which may affect the evaluation of intraocular pressure61 and diagnosis of glaucoma—elaborated further later in this review 62.…”
Section: Introductionmentioning
confidence: 99%